DOP49 Efficacy of the anti-mucosal addressin cell adhesion molecule-1 (MAdCAM-1) antibody SHP647 in ulcerative colitis: results from the open-label extension study TURANDOT II. (25th January 2019) - Reinisch, W; Sandborn, W J; Danese, S; Hébuterne, X; Kłopocka, M; Tarabar, D; Vaňásek, T; Greguš, M; Hellstern, P A; Kim, J S; Sparrow, M; Gorelick, K J; et al.
Abstract: Background: SHP647, a fully human IgG2 monoclonal antibody, binds to MAdCAM-1, reducing lymphocyte homing to the GI tract. In the TURANDOT II trial, SHP647 was well-tolerated and clinical benefit was seen up to 144 weeks in patients with moderate-to-severe ulcerative colitis (UC). This analysis reports efficacy by dose in TURANDOT II, and by prior treatment and response in the TURANDOT induction study. Methods: TURANDOT II (NCT01771809) is a Phase 2, multi-centre, two-part, open-label (OL) study of SHP647 in patients with moderate-to-severe UC who completed TURANDOT on placebo or SHP647 7.5, 22.5, 75, or 225 mg sc every 4 weeks. At TURANDOT II baseline, patients were randomised to SHP647 75 or 225 mg sc every 4 weeks for 72 weeks (OL1). Dose escalation from 75 to 225 mg was permitted at the investigator's discretion from Week 8 to Week 72 in the case of clinical exacerbation or no response. In OL2, all patients received 75 mg every 4 weeks for 72 weeks. Mucosal healing (Mayo endoscopy subscore ≤1), clinical remission (total Mayo score ≤2 with no individual subscore >1, rectal bleed subscore ≤1) and response (based on total Mayo score) were assessed at Week 16 (centrally read endoscopy). Long-term efficacy was assessed by clinical response and remission (partial Mayo score) up to 144 weeks. Results: In total, 330 patients were randomised and treated (SHP647 in TURANDOT, n = 262; placebo in TURANDOT, n = 68). Mucosal healing increased from 20.3% at TURANDOT II baseline (67/330) to 28.5% (94/330) at Week 16 (Figure 1a). Overall, 67 patients (20.3%) were in remission at Week 16, compared with 38 (11.5%) at baseline. Of those not in remission at the end of TURANDOT, 14.0% (41/292) had achieved remission by Week 16 of TURANDOT II—23 of these had been on SHP647 in TURANDOT (23/262; 8.8%) and 18 had been on placebo (18/68; 26.5%). Of patients with clinical response at the end of TURANDOT, 79% maintained response at Week 16; of non-responders in TURANDOT, 38% achieved response by Week 16. Figure 1b shows long-term clinical remission by partial Mayo score; clinical response showed a similar trend. Overall, the mean partial Mayo score improved from 3.8 (SD, 2.29) at TURANDOT II baseline to 1.0 (1.31) at Week 144 in patients who remained in the study ( n = 127). The mean change from TURANDOT baseline to Week 144 was –4.7 (1.73). Conclusions: Clinical response and remission in the induction study continued in the extension study, persisting over the long term in most patients who reached these thresholds. The observed clinical benefit supports continued study of SHP647 in Phase 3 trials.